ACTING SOCIALLY AND QUEST FOR ETHICAL VALUES IN THE EDUCATIONAL CONTEXT - Euphrosyne EFTHIMIADOU (Analele Universităţii din Craiova. Psihologie, Pedagogie, 2025)
In the educational environment, social action as well as the quest for values are in a perpetual evolution. The ethics in education consists of transmitting the sense of otherness, of the human being, which begins with the concern for the Other. It is about knowing how to assess with moderation the uniqueness of situations in the school context, in order to act best by taking into account the ethical intention — the aim of a good and just life — and the moral intention — the norms and principles that serve as guidelines. In this respect, we will begin by looking at the philosophical currents on ethical values in social action. Subsequently, it would be interesting to study the sphere of ethics in education, given that societies are undergoing major changes in search of new values. Finally, we will give a prominent place to the notion of socio-ethical action in pedagogy in order to highlight the close relationship between education and citizenship.